Just about everything you've always wanted to know about tectonics but were afraid to ask - Amaral, Izabel (2009)
The notion of tectonics is not of exclusive use for architecture. There is no doubt that the greater public refers to this term as the theory based on the movement of the continental plates in the field of geology. In architecture, even if the term is increasingly evoked in books, magazines, websites, blogs, and architecture schools, defining tectonics has become even more difficult because its discontinuous presence throughout history has given the term multiple meanings. Frequently defined as the" art of construction", a better understanding of tectonics cannot ignore an understanding of the historical trajectory of the term. A derivative of the greek tekton (carpenter), the notion has more than two thousand years of history. Its understanding changed in relation to its greek origin, mainly due to the contributions of German theoreticians Carl Bötticher and Gottfried Semper in the 19th century, and more recently to the notable contribution of Kenneth Frampton (1983, 1990, 1995, 2005). Frampton renewed the debate on tectonics, promoting the notion to the statute of" expressive potential of construction", capable of congregate material, constructive, cultural, and aesthetic aspects. This paper will begin with a discussion of the evolution of the concept of tectonics, first by considering the emerging technical knowledge of building physics in the 18th century, and then by discussing the two last theoreticians (Semper and Frampton); it concludes by raising current perspectives regarding this notion.